Black Pudding: A Speculative Visual Index: Representational limits of Generative AI during creative porn productions - Petit, Aur´elie (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
Funded by the GenAI Studio grant (Milieux Institute and Applied AI Institute), B̷l̷a̷c̷k̷ P̷u̷d̷d̷i̷n̷g̷ is a research-driven, AI-based project that revisits the lost pornographic animation film Black Pudding (1969) by Nancy Edell (1942-2005), a Canadian-American pioneer director in feminist animation. By using the tools available on generative AI porn platforms, this project speculates on how contemporary AI would represent Black Pudding today. This is done using surviving textual materials (critics, festival reviews, films encyclopedias) written about the film as prompts on contemporary AI-porn content generators. B̷l̷a̷c̷k̷ P̷u̷d̷d̷i̷n̷g̷ creates a space to explore the ethical and creative boundaries of generative AI in reconstituting feminist sexual representations.